2019
DOI: 10.7717/peerj.8210
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and comparative analysis of the complete chloroplast genome sequence from Prunus avium ‘Summit’

Abstract: BackgroundSweet cherry (Prunus avium) is one of the most popular of the temperate fruits. Previous studies have demonstrated that there were several haplotypes in the chloroplast genome of sweet cherry cultivars. However, none of chloroplast genome of a sweet cherry cultivar were yet released, and the phylogenetic relationships among Prunus based on chloroplast genome data were unclear.MethodsIn this study, we assembled and annotated the complete chloroplast genome of a sweet cherry cultivar P. avium ‘Summit’ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 71 publications
(88 reference statements)
0
7
0
Order By: Relevance
“…For this reason, the pseudogene ycf1Ψ was created and overlapped with ndhF. This phenomenon has also been found in other angiosperms, such as Salvia and Prunus 39,40 . Based on the variation of the IR expansion, we were able to divide the Ilex studied into four different groups.…”
Section: Discussionmentioning
confidence: 66%
“…For this reason, the pseudogene ycf1Ψ was created and overlapped with ndhF. This phenomenon has also been found in other angiosperms, such as Salvia and Prunus 39,40 . Based on the variation of the IR expansion, we were able to divide the Ilex studied into four different groups.…”
Section: Discussionmentioning
confidence: 66%
“…Cautleya also possesses the longest LSC region among the included taxa, which suggests that large changes in the rps19 of Cautleya should be the result of LSC region expansion and repair. Previous studies have suggested that rps19 cannot be completely removed from the IRa region through the expansion of LSC or IR regions ( Raman and Park, 2015 ; Lu et al, 2016 ; Zhao X. et al, 2019 ; Androsiuk et al, 2020 ). Therefore, the complete loss of rps19 in Cautleya is more likely than the suppression of rps19 duplication by the LSC region expansion.…”
Section: Discussionmentioning
confidence: 98%
“…The loss of rps19 has also been observed in a few other dicot taxa (e.g., Morus , Nicotiana , Vitis , and Tetrastigma ) but is relatively rare in monocots ( Ravi et al, 2006 ; Li et al, 2015 ), which suggests that rps19 is more likely to be lost or pseudogenized in dicots. The changes in rps19 could be due to (1) partial gene duplication ( Lu et al, 2016 ; Zhao X. et al, 2019 ) or (2) the contraction and expansion of IR regions ( Zhao X. et al, 2019 ). It was suggested that there are two evolutionary mechanisms of the IR region boundary: the small amplitude amplification of the boundary gene and the recombination repair of the boundary of the LSC region.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, seven regions (trnG-GCC -trnR-UCU , trnR-UCU -atpA, psbZ-trnG-GCC , trnH-GUG -psbA, trnT-UGU -trnL-UAA , rpl32-trnL-UAG and trnM-CAU -atpE) showed an unusually high level of variation above 10% (Table 3). In addition, previous study has also showed that rpl32-trnL-UAG exhibited divergence between wild and cultivated sweet cherry (Zhao et al 2019a(Zhao et al , 2019b. Consequently, these regions might be further tested in the studies on population diversity.…”
Section: Discussionmentioning
confidence: 98%
“…We also downloaded 22 available cp genomes of Prunus, comprising P. avium (Zhao et al 2019a), P. campanulata, P. emarginata (Chen et al 2019a), P. cerasoides (Xu et al 2018), P. conradinae (Yan et al 2020), P. dictyoneura (Liu et al 2019), P. dielsiana (Zhao et al 2019b), P. discoidea (Li et al 2019), P. canescens (Chen et al 2019b), P. jamasakura (Yi et al 2020), P. matuurae (Sun and Liu. 2019), P. kumanoensis (Sun et al 2019a), P. maximowiczii, P. pensylvanica (Zhang et al 2019), P. pseudocerasus (Feng et al 2018), P. rufa (Li et al 2020b), P. serrulata, P. spachiana (Sheng et al 2020), P. speciosa (Sun et al 2019b), P. subhirtella, P. takesimensis (Cho et al 2018), and P. yedoensis (Cho et al 2015), then used for subsequent comparative analyses.…”
Section: Data Sourcementioning
confidence: 99%